MODEL SHURIKEN PADA SOCIAL RESPONSIBILITY INDOFOOD RISET NUGRAHA (Studi Kasus Komunikasi Korporasi pada PT. Indofood Sukses Makmur) - Resta Nianda (MediaKom : Jurnal Ilmiah Komunikasi, 2017)
This study discusses CSR program in PT. Indofood Sukses Makmur with a focus on program Indofood Research Nugraha. Indofood Research Nugraha are included in the building pillars of human resources, which is one of the pillars on Social Responsibility PT. Indofood Sukses Makmur. The purpose of this study was to determine the CSR communication strategy Indofood Research Nugraha and provide elaboration regarding CSR programs related to the development of Indofood Research Nugraha student thesis research in Indonesia and reputation received by PT. Indofood Sukses Makmur.To discuss this case of CSR research Indofood Research Nugraha using the concept of strategy, CSR and stakeholder theory. The use of these theories in order to know which way the goals and intent of PT. Indofood Sukses Makmur hold the CSR activities.The object of this research is the scholarship IRN, where the paradigm used in the study was constructivist and research method for this study is qualitative and descriptive approach through the case study method. Secondary data were obtained from key informants and informant by interview and observation. While primary data obtained through library research.Results from this study demonstrate Corporate Social Responsibility Indofood Research Nugraha have a relationship with stakeholders and provide good reputation. There are mutual benefits received by PT. Indofood Sukses Makmur and students. This is explained in the model of shuriken Indofood Research Nugraha.In this study, also PT. Indofood Sukses Makmur realize that they need to keep in touch with alumni grantee Indofood Research Nugraha that students who receive scholarships Indofood Research Nugraha in the current year can make sharing with alumni.Keywords: Corporate Communication Strategy, CSR Indofood Research Nugraha, Qualitative Methods